4D printing of smart polymer nanocomposites: integrating graphene and acrylate based shape memory polymers - Chowdhury, Jaydeep; Anirudh, Premnath Vijay; Karunakaran, Chandrasekaran; Rajmohan, Vasudevan; Mathew, Arun Tom; Koziol, Krzysztof K.; Alsanie, Walaa F.; Kannan, Chidambaram; Balan, Arunachalam S. S.; Thakur, Vijay Kumar (MDPI, 2021)
The ever-increasing demand for materials to have superior properties and satisfy functions in the field of soft robotics and beyond has resulted in the advent of the new field of four-dimensional (4D) printing. The ability of these materials to respond to various stimuli inspires novel applications and opens several research possibilities. In this work, we report on the 4D printing of one such Shape Memory Polymer (SMP) tBA-co-DEGDA (tert-Butyl Acrylate with diethylene glycol diacrylate). The novelty lies in establishing the relationship between the various characteristic properties (tensile stress, surface roughness, recovery time, strain fixity, and glass transition temperature) concerning the fact that the print parameters of the laser pulse frequency and print speed are governed in the micro-stereolithography (Micro SLA) method. It is found that the sample printed with a speed of 90 mm/s and 110 pulses/s possessed the best batch of properties, with shape fixity percentages of about 86.3% and recovery times as low as 6.95 s. The samples built using the optimal parameters are further subjected to the addition of graphene nanoparticles, which further enhances all the mechanical and surface properties. It has been observed that the addition of 0.3 wt.% of graphene nanoparticles provides the best results.
Keywords: 4D printing; shape memory polymer; strain fixity; graphene